Draft genome of Thermomonospora sp. CIT 1 (thermomonosporaceae) and in silico evidence of its functional role in filter cake biomass deconstruction - Omori, Wellington P. [UNESP]; Pinheiro, Daniel G. [UNESP]; Kishi, Luciano T. [UNESP]; Fernandes, Camila C. [UNESP]; Fernandes, Gabriela C. [UNESP]; Gomes-Pepe, Elisângela S. [UNESP]; Pavani, Claudio D. [UNESP]; Lemos, Eliana G. de M. [UNESP]; de Souza, Jackson A. M. [UNESP] (FapUNIFESP (SciELO), 2019)
The filter cake from sugar cane processing is rich in organic matter and nutrients, which favors the proliferation of microorganisms with potential to deconstruct plant biomass. From the metagenomic data of this material, we assembled a draft genome that was phylogenetically related to Thermomonospora curvata DSM 43183, which shows the functional and ecological importance of this bacterium in the filter cake. Thermomonospora is a gram-positive bacterium that produces cellulases in compost, and it can survive temperatures of 60 ºC. We identified a complete set of biomass depolymerizing enzymes in the draft genome of Thermomonospora sp. CIT 1, such as α-amylase, catalase-peroxidases, β-mannanase, and arabinanase, demonstrating the potential of this bacterium to deconstruct the components of starch, lignin, and hemicellulose. In addition, the draft genome of Thermomonospora sp. CIT 1 contains 18 genes that do not share identity with five other species of Thermomonospora, suggesting that this bacterium has different genetic characteristics than those present in genomes reported so far for this genus. These findings add a new dimension to the current understanding of the functional profile of this microorganism that inhabits agro-industrial waste, which may boost new gene discoveries and be of importance for application in the production of bioethanol.
Keywords: Actinobacteria; Crystalline cellulose; Hemicellulose; Orthologous genes; Pectin